The Kaiser's Mosques: Islamic Architecture and Orientalizing Style in Habsburg Bosnia, 1878–1918 - Hartmuth, Maximilian (Studies in Central European Culture, 2024)
This book highlights an understudied experiment at the intersection of 19th-century European and Islamic architectural histories. It draws attention to a body of buildings designed by architects trained in Central Europe for use by Muslims in Habsburg ruled Bosnia-Herzegovina (1878-1918). They include mosques, madrasas, and other buildings corresponding to a traditional Islamic formal and functional typology. The composition and decoration, however, is the product of 19th-century European His toricist conduct. It became a prominent style for town halls and private residences; on occasion, it was also used for railway stations, schools, or hotels. The spread and concentration of buildings in this style in Bosnia is extraordinary. This monography not only fills a gap in an art history that has long turned a blind eye to Europe’s Southeast but also contributes to our understanding of European powers’ historical responses to the challenge of cultural diversity in territories under their control